A sucessão na empresa familiar: a importância do planejamento do processo sucessório nas empresas familiares - Tavares, Núbia Crístian Gomes França (Universidade do Vale do Rio dos Sinos, 2022)
This research has as its theme the Planning of the Succession Process in Family Businesses. In most family businesses, succession is a crucial issue, and cannot be decided exclusively through inventory or sharing. The second generation inherits a built-up company, needing to prepare for the category of partner it will take on, with the need to settle expectations and particular fears. As such, it is imperative to create a corporate atmosphere in which family members experience security in their new shared capacity. Business succession is an intricate process that considers the transfer of capital on the one hand and the transfer of ownership on the other. The most used paths for succession are the will, donations and holding companies, aiming at the concentration of family assets, holding the equity interest and, in this way, separating operation and control, seeking to isolate the company's family conflicts. In the first chapter we have the introduction. Then, in the second chapter, we systematize a theoretical reflection that incorporates some considerations about family business and the death of the founder. In the third chapter, we talk about professionalization, sustainability and the standard clauses for the realization of the shareholders' agreement, aimed at the company's success and continuity for future generations. Finally, final considerations. The present research had as general objectives to show the difficulties encountered by founders in passing power and command to their descendants, researching measures in order to guarantee their continuity. As specific objectives, we seek to assess the causes that lead family businesses to crises that cause their vulnerability, even leading to their disappearance, what preventive actions have already been developed by professionals in the area, demonstrating when and what time to occur, the need to raise awareness about the importance of this succession planning, exposing tools that help; thus mitigating the conflicts between future generations, which emerge at this stage in the life of these companies. Thus, we also seek to highlight the importance of the professionalization of the heirs to face the complex trajectory before the position of managers, in order to continue the family businesses beyond the 2nd generation. The results obtained from this research were extremely important for understanding why a large number of family businesses do not resist, most of the time, to future generations, demonstrating that succession planning can guarantee the continuity of organizations. The applied methodology was deductive, starting from general concepts and categories for the specific treatment of the research object. The research techniques were the bibliographic review, national and foreign, as well as data collection and documents submitted to theoretical analysis. The research has as its theoretical delivery the creation of an extension course at the UniRV law school, with the target audience being businessmen, laypeople and legal professionals.
Keywords: Empresa familiar; Sucessão; Planejamento sucessório; Family business; Succession; Succession planning; ACCNPQ::Ciências Sociais Aplicadas::Direito